Effect of Cutouts on the Behavior of Clamped Rectangular Plates - Yahya Rzayyig, Arz (Anbar Journal of Engineering Sciences, 2011)
Plates with interior openings are often used in both modern and classical aerospace, mechanical and civil engineering. The understanding of the effects of two cutouts on the stress concentration factor, maximum stress and deflections in perforated clamped rectangular plates, were considered. Parameters such as location, size of cutout and the aspect ratio of plates are very important in designing of structures. These factors were presently studied and solved by finite element method (ANSYS) program. The results based on numerical solution were compared with the results obtained from different analytical solution methods. One of the main objectives of this study is to demonstrate the accuracy of the analytical solution for clamped square plate. In general, the results of the square clamped plates with two cutouts come out in good agreement. The results presented here indicated that the maximum stress, deflection of perforated plates can be significantly changed by using proper cutouts locations and/or size. The results show that the rectangular plate containing two cutouts arranged along the width is stronger and stiffer than when arranged along the length at a given spacing, and the square plate is always stronger and stiffer than an equivalent rectangular plate for the same loading condition.